2016
DOI: 10.5603/kp.a2016.0040
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic ultrasonic tissue indices identify patients with severe left anterior descending artery stenosis. Correlation with fractional flow reserve. Pilot study

Abstract: A b s t r a c t Background and aim:The aim of this study was to evaluate the potential clinical application of ultrasonic tissue indices, with a focus on systolic strain (SS) and systolic strain rate (SSR) parameters derived from transthoracic echocardiography, in the assessment of left anterior descending artery (LAD) stenosis. Methods:The data of 30 patients with significant LAD stenosis were analysed. All patients underwent transthoracic echocardiography to obtain systolic myocardial velocity (Sm), longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Regional myocardial dysfunction caused by coronary stenosis can be detected by two-dimensional speckle tracking echocardiography ( 3 , 4 ). In stable patients, the longitudinal strain is useful for the detection of functionally significant CADs, which has been confirmed by invasive FFR ( 5 7 ). However, because of the load-dependent nature of myocardial strain, the interpretation of the myocardial functional status based on strain analysis has to be made in a context of ventricular loading conditions ( 8 ).…”
Section: Introductionmentioning
confidence: 86%
“…Regional myocardial dysfunction caused by coronary stenosis can be detected by two-dimensional speckle tracking echocardiography ( 3 , 4 ). In stable patients, the longitudinal strain is useful for the detection of functionally significant CADs, which has been confirmed by invasive FFR ( 5 7 ). However, because of the load-dependent nature of myocardial strain, the interpretation of the myocardial functional status based on strain analysis has to be made in a context of ventricular loading conditions ( 8 ).…”
Section: Introductionmentioning
confidence: 86%
“…The researchers found that the patients with significant CAD had significantly reduced rest GLS, but not LVEF or end-diastolic volume, compared to those with non-obstructive CAD. Dobrowolski et al [15] evaluated 30 patients with significant LAD stenosis confirmed by FFR values ≤ 0.8. The study compared anterior and inferior walls in the two-chamber apical view in the same group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dobrowolski et al [ 15 ] evaluated 30 patients with significant LAD stenosis confirmed by FFR values ≤ 0.8. The study compared anterior and inferior walls in the two-chamber apical view in the same group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation